Christomatric Mission: A Pastoral-Theological Model for Christian Witness in Pluralistic Societies - Nweke, Kizito Chinedu (UIN Sunan Gunung Djati Bandung, 2024)
This study explores how African Christians in Germany navigate the tension between maintaining their confessional identity and engaging in increasingly pluralistic and secular societies. Recognising the pastoral and theological challenges posed by epistemological relativism and interreligious equality, the research introduces the Christomatric Model as a relational framework for Christian missions. Employing a qualitative methodology with a reflective-hermeneutic approach, data were collected through informal conversations, participant observation, and written reflections within the African Catholic Community in Mannheim. Thematic analysis revealed that believers frequently moderate their expressions of faith—avoiding exclusivist language, concealing religious symbols, and adopting neutral terminology—due to fear of rejection or social stigmatisation. These findings underscore Christians' internal and external pressures in pluralistic settings and highlight the need for alternative pastoral strategies. The Christomatric Model responds by reframing Christian witness as relational accompaniment rather than doctrinal confrontation, offering a theologically grounded and contextually sensitive approach that upholds faith integrity while fostering interfaith respect. This study contributes original insights into contextual missiology by shifting the mission's focus from conversion to presence and by providing a concrete theological response to the lived experiences of believers in pluralistic societies. Its originality lies in articulating a mediatory paradigm that integrates doctrinal fidelity with relational openness, filling a significant gap in current theological and pastoral discourse.